2011
DOI: 10.1101/lm.2126111
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic receptors in the insular cortex are differentially involved in aversive vs. incidental context memory formation

Abstract: The goal of this research was to determine the effects of b-adrenergic antagonism in the IC before or after inhibitory avoidance (IA) training or context pre-exposure in a latent inhibition protocol. Pretraining intra-IC infusion of the b-adrenergic antagonist propranolol disrupted subsequent IA retention and impaired latent inhibition of IA, but had no effect on formation of memory for an inert context (termed incidental memory). These results indicate that IC b-adrenergic receptors are necessary for memory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…b-ARs include three subtypes, b1, b2, and b3, which are all present in the nervous system. Extensive behavioral and physiological studies have demonstrated that b-AR activation facilitates long-term potentiation (LTP) (Katsuki et al 1997;Lin et al 2003;Straube et al 2003;Gelinas and Nguyen 2005;O'Dell et al 2010;Connor et al 2011) and enhances memory (Ji et al 2003;Tronel et al 2004;Lemon et al 2009;Miranda et al 2011).…”
mentioning
confidence: 99%
“…b-ARs include three subtypes, b1, b2, and b3, which are all present in the nervous system. Extensive behavioral and physiological studies have demonstrated that b-AR activation facilitates long-term potentiation (LTP) (Katsuki et al 1997;Lin et al 2003;Straube et al 2003;Gelinas and Nguyen 2005;O'Dell et al 2010;Connor et al 2011) and enhances memory (Ji et al 2003;Tronel et al 2004;Lemon et al 2009;Miranda et al 2011).…”
mentioning
confidence: 99%